2016
DOI: 10.1037/tps0000079
|View full text |Cite
|
Sign up to set email alerts
|

Celebrities emerge as advocates in tweets about bullying.

Abstract: To understand the ways that social media users connect with celebrities about bullying, 1,280,151 posts that mentioned one of the top 302 celebrity users named within bullying keyword posts on Twitter between January 1, 2012 and December 31, 2012 were analyzed. Social science and computer science methods were combined to identify how individuals defined celebrities according to bullying roles and what features of celebrities and the tweets were related to the bullying roles. The results show that Twitter users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…These URL sites provided useful information including support for victims and strategies for dealing with cyberbullying. Similarly, Resnik et al’s (2016) analysis of tweets showed that tweets containing references to celebrities in an advocate role, that is, as someone who might take or who has taken a general antibullying stance, were largely positive in sentiment. These suggest that multiple avenues exist to combat cyberbullying messages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These URL sites provided useful information including support for victims and strategies for dealing with cyberbullying. Similarly, Resnik et al’s (2016) analysis of tweets showed that tweets containing references to celebrities in an advocate role, that is, as someone who might take or who has taken a general antibullying stance, were largely positive in sentiment. These suggest that multiple avenues exist to combat cyberbullying messages.…”
Section: Discussionmentioning
confidence: 99%
“…Computer scientists have focused on cyberbullying primarily through the development of methods to detect or block aggressive texts as well as user interfaces that encourage reflection by the perpetrator before engaging in aggressive behavior (Al-garadi et al, 2016; Raman et al, 2015). To a lesser extent, researchers have analyzed the content of tweets such as sentiment (Choi et al, 2014; Resnik, Bellmore, Xu, & Zhu, 2016), hashtags (Calvin et al, 2015), and the role of the audience or online bystanders (Cocea, 2016). Previous Twitter research suggests that each approach to text analysis includes both strengths and weakness, for example, machine learning faces challenges when coding slang and “informal text” (Del Bosque & Garza, 2014), while human analysis might include personal bias due to individual experience.…”
mentioning
confidence: 99%
“…Such technologies make detection of social bots more difficult and provide an advantage to the bot creators in this arms race. Targeted attacks are made possible through the anonymous use of social media, by orchestrating a large army of social bots, trolls (McCosker, 2014;Aro, 2016), sock puppets, and bullies (Bellmore et al, 2015;Resnik et al, 2016). Examples of extremist activities on social media have been increasing at an alarming rate, and many platforms have started taking precautions for early-detection and prevention of such activities.…”
Section: Discussionmentioning
confidence: 99%
“…We focus on Twitter because it is a straightforward source of large volumes of online social networks data and provides a public REST API for collecting the streams of tweets. 3 While some datasets are available for detecting other types of cyberbullying on Twitter [10,41], they have not focused on doxing and sensitive information disclosure specifically. Therefore, they mostly do not contain any sensitive information, and we had to collect a new set of tweets.…”
Section: Building a Doxing Datasetmentioning
confidence: 99%